An Amanah Approach of Supervision Model to Improve the Performance of Islamic Education Teachers at Public Junior High Schools in Nagan Raya - Herman, Jamaluddin Idris, Nur Asiah, Nur Anifah, Hasnadi (International Journal of Advanced Science and Technology, 2020)
An Amanah Approach of Supervision Model to Improve the Performance of Islamic Education (PAI) Teachers is one of the value-based approaches to amanah values as a guiding principle for working, identity-building action and the moral force for PAI supervisors in performing their primary duties and monitoring functions towards PAI teachers. The problem is that PAI supervisors are still a long way from amanah attitudes and behaviors in guiding, promoting and improving the performance of PAI teachers. This research used a descriptive method as well as a qualitative approach and data collection techniques through: observation, interviews and documentation studies. In addition, data analysis techniques related to the opinion of Miles and Huberman through data reduction, data presentation, and inference. While the validity of the data was checked by source triangulation, method triangulation and theoretical triangulation. The results showed that the PAI supervisors had used the amanah approach of working models that are subject to and obey religious and state law, working models that are full of responsibility, working models that are faithful to the task, working models that deliver on the promise, and working models that are full of honesty. Although this approach has been used by PAI supervisors, it has turned out that their identity has not yet been established, namely to work with full loyalty and responsibility to improve the performance of PAI teachers.